France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper analyzes the performance of French banks and the financial support measures taken by the French government. France has a large and sophisticated financial system, which accounts for 10 percent of the global banking system and 5 percent of global capital markets. This paper presents an overview of the French banking and supervision structure. It conducts comparative analyses of profitability, asset quality, capital adequacy, leverage, quality of capital, funding profile, and liquidity of banks. The paper also analyzes business lines, potential spillovers, and market perceptions of risk.